Design and Experimental Verification of Hip Exoskeleton With Balance Capacities for Walking Assistance - Zhang, Ting; Tran, Minh; Huang, He (IEEE/ASME transactions on mechatronics, 2018)
Most current hip exoskeletons emphasize assistance for walking rather than stability. The goal of this paper is to develop a novel, high-power, self-balancing, and passively and software-controlled actively compliant hip exoskeleton that can assist with movement and maintain balance in both the sagittal and frontal planes. The developed hip exoskeleton includes powered hip abduction/adduction and hip flexion/extension joints. Each actuation unit employs a modular and compact series elastic actuator (SEA) with a high torque-to-weight ratio. It provides mechanical compliance at the interface between the exoskeleton and the wearer to ensure safety and a natural gait in the coupled wearer-exoskeleton system. A new balance controller based on the extrapolated center of mass concept is presented for maintaining walking stability. This controller reacts to perturbations in balance and produces a compliant guidance force through a combination of the passive elasticity of the SEA and active compliant control based on adaptive admittance control. The function of the hip exoskeleton is not to override human control, but rather to involve the wearer in movement control in order to avoid conflicts between wearer and exoskeleton. Our preliminary experiments on a healthy subject wearing the hip exoskeleton demonstrate the potential effectiveness of the proposed hip exoskeleton and controller for walking balance control.